RANCANG BANGUN SISTEM INFORMASI PPDB BERBASIS WEB PADA SMAK BHAKTI LUHUR MALANG MENGGUNAKAN MODEL PROTOTYPE - Supaat, Supaat; Setiyaningsih, Wiji; Syahminan (Department of System Information, 2024)
Catholic High School (SMAK) at Bhakti Luhur Malang, is one of the Catholic religious-based high schools, in accepting new students (PPDB) it still uses a conventional system by sending and returning forms using couriers, sometimes it still needs to be re-confirmed for availability. Lack of registration requirements and the process of resubmitting these requirements are carried out. As a solution to this problem, this research created a design for a WEB-based PPDB information system at SMAK Bhakti Luhur Malang using a prototype model. The system was built by inputting the registration form and uploading student requirements documents. PPDB officers check the requirements, if there are any deficiencies they will be reconfirmed via e-mail and if they are complete then the registration will be accepted with notification via e-mail, students can check their registration status independently. The average UAT results from the research and development of this system reached 94%, indicating that the functions of the system were declared suitable for using as a PPDB information system at SMAK Bhakti Luhur Malang.